“Efecto de hongos microorízicos arbusculares nativos sobre el nematodo agallador de raices (meloidogyne spp.) en plantones de café (coffea arabica) variedad caturra en la región de San Martín - Chinchay Rubio, Decny Omar (2016)
Nowadays the use of microorganisms in agricultura is one of the alternativa solutions to reduce the use of chemicals products. The arbuscular mycorrhizal fungi (AMF) are soil fungi, which form mutualistic symbiosis with the roots of most plants, including the coffee, providing excellent benefits. The objective of this research was to determine the effect of different sources of inoculum of nativa AMF on root-knot nematode (Meloidogyne spp.) in coffee seedlings (Coffea arabica) variety caturra in the region San Martin.